2004
DOI: 10.1007/s00213-003-1627-3
|View full text |Cite
|
Sign up to set email alerts
|

d -Amphetamine responses in catechol-O-methyltransferase (COMT) disrupted mice

Abstract: Changes in COMT activity modulates dopamine metabolism but the behavioral effects of d-amphetamine in male mice only to a small extent, and this action does not seem to depend on the actual extracellular dopamine concentration. Nor is it mediated through compensatory changes in dopamine D(1) and D(2) receptor levels. In dopaminergic neurons, the contribution of intracellular COMT remains secondary in conditions when dopamine is released by d-amphetamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 36 publications
4
38
0
Order By: Relevance
“…Although local effects of COMT in the ventral striatum have been hypothesized (13), current evidence (17) favors an explanation based on prefrontal regulation of striatal DA metabolism via top-down projections (16).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although local effects of COMT in the ventral striatum have been hypothesized (13), current evidence (17) favors an explanation based on prefrontal regulation of striatal DA metabolism via top-down projections (16).…”
Section: Discussionmentioning
confidence: 87%
“…COMT is known to regulate extrasynaptical DA breakdown, which is mainly true for the prefrontal cortex (PFC), where COMT is relatively more abundant than in the striatum (16). COMT might also have a small, local effect in DA metabolism in the striatum (17). More importantly, an interaction between prefrontal COMT and subcortical function has been suggested (12), probably mediated by excitatory glutamatergic efferents from the PFC to the striatum, which are thought to translate a high prefrontal into a high striatal dopaminergic tone (13).…”
mentioning
confidence: 99%
“…Further studies in the COMT knockout mice, using cocaine, GBR 12909 (a dopamine transporter inhibitor), levodopa, or amphetamine, showed that some but not all neurochemical and behavioral responses to these pharmacological challenges are sex specific (Huotari et al, 2002a(Huotari et al, , b, 2004see also O'Tuathaigh et al, 2007). For example, d-amphetamine administration affected dopamine metabolism equally in male and female knockout mice (Huotari et al, 2004), whereas hyperactivity in response to GBR 12909 was attenuated only in male mice (Huotari et al, 2002b).…”
Section: Comt and Sexual Dimorphismsmentioning
confidence: 99%
“…The quantitative contribution of COMT to dopamine degradation is under debate, with several studies suggesting that its role is secondary to that of dopamine reuptake and oxidation by monoamine oxidase A and B (Budygin et al, 1999;Huotari et al, 2002Huotari et al, , 2004. These studies have focused on dopamine metabolism in the striatum in which DAT1 expression is abundant.…”
Section: Effects Of Comt Val108/158met Genotype On Memoryrelated Braimentioning
confidence: 99%